Palladium nanoparticle-graphene composite structure, preparation method and application thereof, and hydrogen sensor
By depositing palladium nanofilms on graphene films and then subjecting them to heat treatment and activation, a palladium nanoparticle-graphene composite structure is formed, which solves the problems of low sensitivity and slow recovery speed of existing hydrogen sensors at room temperature. This enables high-sensitivity detection and rapid recovery of ppb-level hydrogen, making it suitable for commercial applications of hydrogen sensors.
Patent Information
- Application Number
- CN202511000222.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-10-21
AI Technical Summary
Existing hydrogen sensors use metal oxides as hydrogen-sensitive materials, which have poor selectivity, low sensitivity, and need to operate above 200°C, making it difficult to accurately detect hydrogen at room temperature. In addition, existing palladium-graphene composite hydrogen sensors have low sensitivity, long recovery time, and poor repeatability, making it difficult to detect ppb-level hydrogen.
A palladium nanofilm was deposited on a graphene film and subjected to heat treatment and activation to form a palladium nanoparticle-graphene composite structure. An ordered microsphere template was constructed using a gas-liquid interface self-assembly process. Combined with a hydrogenation-oxidation strategy, the distribution of palladium nanoparticles on graphene and the interfacial oxygen groups were regulated to optimize the hydrogen diffusion path and improve the sensitivity and recovery speed of the sensor.
It achieves high-sensitivity detection of ppb-level hydrogen at room temperature, with rapid recovery and high accuracy, making it suitable for commercial applications of hydrogen sensors.
Smart Images

Figure CN120818808A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen sensors, and in particular relates to a palladium nanoparticle-graphene composite structure, a preparation method and application thereof, and a hydrogen sensor. Background Art
[0002] Hydrogen, a readily available, green, low-carbon, and widely applicable secondary energy source, is becoming a key driver of the current energy transition. However, hydrogen's low density, rapid diffusion rate, and wide range of explosion limits in air (4.0% to 75.6%) make it susceptible to leakage and highly explosive when exposed to open flames or high temperatures. Therefore, the use of high-performance hydrogen sensors to promptly detect hydrogen leaks is crucial for ensuring the safe use of hydrogen.
[0003] Hydrogen sensors currently on the market primarily use metal oxides as hydrogen-sensitive materials. These materials suffer from poor selectivity, low sensitivity, and the requirement to operate at temperatures above 200°C, making room-temperature hydrogen monitoring difficult. Accuracy and safety also need to be improved. Palladium has a strong hydrogen absorption capacity, while graphene possesses a high specific surface area, excellent conductivity, and mechanical strength. This high specific surface area provides more attachment sites for palladium nanoparticles, improving the sensitivity of hydrogen sensors. Its excellent conductivity reduces resistive losses and accelerates carrier transport, enabling rapid sensor response and low-concentration hydrogen detection. Combining palladium nanoparticles with graphene thin films as a hydrogen-sensitive sensing layer theoretically combines palladium's high catalytic activity for hydrogen with the advantages of graphene's two-dimensional structure. However, while existing hydrogen sensors based on palladium-graphene composites have achieved room-temperature detection, they still suffer from low sensitivity, long recovery times, and poor reproducibility, making it difficult to detect hydrogen at the ppb level. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide a palladium nanoparticle-graphene composite structure, its preparation method and application, and a hydrogen sensor. The palladium nanoparticle-graphene composite structure prepared by the present invention has high sensitivity, selectivity, recovery speed and repeatability for hydrogen detection, and can achieve ppb-level hydrogen detection at room temperature with high accuracy and good safety.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a palladium nanoparticle-graphene composite structure, including method one, method two or method three;
[0007] The method 1 comprises the following steps:
[0008] After plating a palladium nanofilm on a substrate covered with a graphene film, heat treatment and repeated activation treatment are performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0009] The activation treatment is carried out by hydrogenation treatment in a reducing atmosphere and oxidation treatment in an oxygen-containing atmosphere in sequence;
[0010] The second method comprises the following steps:
[0011] The suspension of polymer microspheres is self-assembled in water through the air-liquid interface to form a polymer microsphere array;
[0012] The polymer microsphere array is pulled out using a substrate covered with a graphene film, so that the polymer microsphere array and the graphene film overlap, and dried to obtain a polymer microsphere-graphene composite film;
[0013] After plating a palladium nanofilm on the polymer microsphere array of the polymer microsphere-graphene composite film, heat treatment is performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0014] The method three comprises the following steps:
[0015] The product after heat treatment in the second method is repeatedly activated to obtain a palladium nanoparticle-graphene composite structure.
[0016] Preferably, the polymer microspheres are polyethylene microspheres; the particle size of the polymer microspheres is 20 nm to 5 μm.
[0017] Preferably, the palladium nanofilm has a thickness of 3 to 100 nm.
[0018] Preferably, the reducing atmosphere comprises hydrogen and argon; the flow rate of the hydrogen is 5 to 50 sccm; the flow rate of the argon is 20 to 100 sccm; the temperature of the hydrogenation treatment is 300 to 650° C., and the holding time is 10 to 60 minutes.
[0019] Preferably, the oxygen-containing atmosphere includes oxygen and argon; the oxygen content in the oxygen-containing atmosphere is 1 to 100 ppm; the flow rate of the oxygen-containing atmosphere is 10 to 200 sccm; the temperature of the oxidation treatment is 300 to 650° C., and the holding time is 5 to 60 minutes.
[0020] Preferably, the heat treatment temperature is 400-650° C., the holding time is 1-3 hours, and the heating rate to the heat treatment temperature is 5-20° C. / min.
[0021] Preferably, the palladium nanofilm is deposited by electron beam deposition, thermal evaporation deposition or magnetron sputtering deposition.
[0022] The present invention also provides a palladium nanoparticle-graphene composite structure prepared by the preparation method described in the above technical solution, comprising a graphene film, palladium nanoparticles bonded to the surface of the graphene film through Pd-C bonds, and oxygen-containing groups modified on the surface of the graphene film;
[0023] When the preparation method is method 1, the average particle size of the palladium nanoparticles is 40 to 80 nm, the coverage is 15 to 30%, and the atomic proportion of the oxygen-containing groups in the graphene film is 15 to 50%.
[0024] When the preparation method is method 2, the palladium nanoparticles include large-diameter palladium nanoparticles arranged in a hexagonal pattern and small-diameter palladium nanoparticles dispersed between the large-diameter palladium nanoparticles; the difference in particle size between the large-diameter palladium nanoparticles and the small-diameter palladium nanoparticles is 5 to 400 nm; the coverage of the palladium nanoparticles is 20 to 80%; and the atomic proportion of the oxygen-containing groups in the graphene film is 1 to 15%.
[0025] When the preparation method is method three, the palladium nanoparticles include large-size palladium nanoparticles arranged in a hexagonal pattern and small-size palladium nanoparticles dispersed between the large-size palladium nanoparticles; the particle size difference between the large-size palladium nanoparticles and the small-size palladium nanoparticles is 5 to 400 nm; the oxygen-containing groups are distributed around the contact interface between the graphene film and the palladium nanoparticles; the coverage rate of the palladium nanoparticles is 20 to 80%; and the atomic proportion of the oxygen-containing groups in the graphene film is 15 to 50%.
[0026] The present invention also provides an application of the palladium nanoparticle-graphene composite structure described in the above technical solution in a hydrogen sensor.
[0027] The present invention also provides a hydrogen sensor, comprising a palladium nanoparticle-graphene composite structure and electrodes deposited at both ends of the surface of the palladium nanoparticle-graphene composite structure; the palladium nanoparticle-graphene composite structure is the palladium nanoparticle-graphene composite structure described in the above technical solution.
[0028] The present invention provides a method for preparing a palladium nanoparticle-graphene composite structure, including method one, method two or method three;
[0029] The method 1 comprises the following steps:
[0030] After plating a palladium nanofilm on a substrate covered with a graphene film, heat treatment and repeated activation treatment are performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0031] The activation treatment is sequentially performing a hydrogenation treatment in a reducing atmosphere and an oxidation treatment in an oxygen-containing atmosphere;
[0032] The second method comprises the following steps:
[0033] The suspension of polymer microspheres is self-assembled in water through the air-liquid interface to form a polymer microsphere array;
[0034] The polymer microsphere array is pulled out using a substrate covered with a graphene film, so that the polymer microsphere array and the graphene film overlap, and dried to obtain a polymer microsphere-graphene composite film;
[0035] After plating a palladium nanofilm on the polymer microsphere array of the polymer microsphere-graphene composite film, heat treatment is performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0036] The method three comprises the following steps:
[0037] The product after heat treatment in the second method is repeatedly activated to obtain a palladium nanoparticle-graphene composite structure.
[0038] The present invention constructs an ordered microsphere template on the graphene surface through a gas-liquid interface self-assembly process, plates a palladium nanofilm on the microsphere array, and then performs heat treatment to make palladium nanoparticles regularly and evenly bonded to the graphene. The palladium nanoparticles include large-diameter palladium nanoparticles arranged in a hexagonal pattern and small-diameter palladium nanoparticles dispersed between the large-diameter palladium nanoparticles. The palladium nanoparticles have a high coverage rate on the graphene carrier surface and are not easy to agglomerate, thereby realizing the regulation of the size distribution of the palladium nanoparticles, breaking through the limitation of random nucleation of metal particles in traditional loading processes, and solving the technical problems of low coverage rate and easy agglomeration of palladium nanoparticles on the graphene carrier surface. The contact area and active site density of the palladium nanoparticle-graphene interface are significantly improved, which is beneficial to the electron transfer among palladium, hydrogen, and graphene during the hydrogen response process. Furthermore, to address the slow recovery rate caused by the strong Pd-H bond during hydrogen sensing, the present invention proposes a hydrogenation-oxidation strategy, leveraging the dynamic, reversible process of palladium volume expansion upon hydrogen absorption and contraction upon dehydrogenation to induce graphene lattice distortion. Combined with the action of low-concentration oxygen, this creates localized oxygen species-modified sites on the graphene at the interface, significantly reducing the hydrogen overflow barrier. This promotes the migration of hydrogen atoms from the palladium surface into the graphene carrier, effectively inhibiting the deep diffusion of hydrogen into the palladium bulk, and significantly improving the sensitivity and recovery rate of the hydrogen sensor. This method effectively modulates the palladium-graphene interface structure without affecting graphene far from the interface, thereby maximizing the advantages of graphene's excellent electrical properties, such as high carrier mobility. Under the dual mechanisms of interfacial oxygen groups optimizing hydrogen diffusion paths and high-density active sites improving hydrogen diffusion efficiency, the sensor has broken through the performance limits of a single modification strategy and achieved synergistic gains in sensing performance. The hydrogen sensor made using a palladium nanoparticle-graphene composite structure has both ultra-high sensitivity and excellent performance of rapid and complete recovery at room temperature, achieving ppb-level hydrogen detection at room temperature with high accuracy and good safety, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is an optical micrograph of the graphene film transferred onto the Si / SiO2 substrate in Example 1;
[0040] Figure 2 is the Raman graph of the graphene film after transfer in Example 1;
[0041] Figure 3 Schematic diagram of the process flow for obtaining highly dispersed palladium nanoparticles using the PS microsphere array template method in Example 2;
[0042] Figure 4 This is a SEM image of the PS microsphere (1 μm in diameter) array on the graphene film surface in Example 2;
[0043] Figure 5This is a SEM image of the PS microsphere (diameter 500 nm) array on the graphene film surface in Example 3;
[0044] Figure 6 This is a SEM image of the PS microsphere (diameter 100 nm) array on the graphene film surface in Example 4;
[0045] Figure 7 This is an SEM image of the palladium nanoparticles in the palladium nanoparticle-graphene composite film prepared in Example 5;
[0046] Figure 8 This is an SEM image of the palladium nanoparticles in the palladium nanoparticle-graphene composite structure prepared in Example 6;
[0047] Figure 9 This is a statistical diagram of the particle size distribution of palladium nanoparticles in the palladium nanoparticle-graphene composite structure prepared in Example 6;
[0048] Figure 10 The average size and coverage of palladium nanoparticles prepared using PS microspheres with different diameters as templates;
[0049] Figure 11 Graph showing the response behavior of the hydrogen sensors in Examples 7 and 8 to 2 vol% H2 at room temperature;
[0050] Figure 12 The palladium nanoparticle-graphene composite film (Pd-Gr) prepared in Example 5 and the palladium nanoparticle-graphene composite structure (Pd-Gr-O H20% )’s XPS C 1s pattern;
[0051] Figure 13 This is a physical picture and schematic diagram of the hydrogen sensor;
[0052] Figure 14 Response and recovery behavior diagram of the hydrogen sensor prepared in Example 9 to 2% H2 at room temperature;
[0053] Figure 15 The palladium nanoparticle-graphene composite structure (Pd PS -Gr) and the palladium nanoparticle-graphene composite structure prepared in Example 10 (Pd PS -Gr-O H20% )’s XPS C 1s pattern;
[0054] Figure 16 This is a graph showing the response and recovery behavior of the hydrogen sensor prepared in Example 10 to 10 ppb-2% H2 at room temperature;
[0055] Figure 17This is a test graph of the repeatability response of the hydrogen sensor prepared in Example 10 to 100 ppm H2 at room temperature;
[0056] Figure 18 This is a selectivity test graph of the hydrogen sensor prepared in Example 10 for 100 ppm H2, NH3, CO, SO2, and CH4 at room temperature;
[0057] Figure 19 This is a graph showing the response and recovery behavior of the hydrogen sensor prepared in Example 11 to 1 ppb-2% H2 at room temperature. DETAILED DESCRIPTION
[0058] The present invention provides a method for preparing a palladium nanoparticle-graphene composite structure, including method one, method two or method three;
[0059] The method 1 comprises the following steps:
[0060] After plating a palladium nanofilm on a substrate covered with a graphene film, heat treatment and repeated activation treatment are performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0061] The second method comprises the following steps:
[0062] The suspension of polymer microspheres is self-assembled in water through the air-liquid interface to form a polymer microsphere array;
[0063] The polymer microsphere array is pulled out using a substrate covered with a graphene film, so that the polymer microsphere array and the graphene film overlap, and dried to obtain a polymer microsphere-graphene composite film;
[0064] After plating a palladium nanofilm on the polymer microsphere array of the polymer microsphere-graphene composite film, heat treatment is performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0065] The method three comprises the following steps:
[0066] Repeating the activation treatment on the product after the heat treatment in the second method to obtain a palladium nanoparticle-graphene composite structure;
[0067] The activation treatment is a hydrogenation treatment in a reducing atmosphere and an oxidation treatment in an oxygen-containing atmosphere in sequence.
[0068] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art can be used.
[0069] The method provided by the present invention comprises the following steps:
[0070] After plating a palladium nanofilm on a substrate covered with a graphene film, heat treatment and repeated activation treatment are performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure;
[0071] The activation treatment is a hydrogenation treatment in a reducing atmosphere and an oxidation treatment in an oxygen-containing atmosphere in sequence.
[0072] As an embodiment, the method for preparing the substrate covered with a graphene film comprises the following steps:
[0073] A graphene film is grown on the pretreated copper foil surface using chemical vapor deposition;
[0074] Spin coating a transfer medium on the surface of the copper foil on which the graphene film is grown, and curing the medium to form a support layer, thereby obtaining a support layer-graphene film-copper foil composite structure;
[0075] After etching the support layer-graphene film-copper foil composite structure in an etching solution to remove the copper foil, the floating support layer-graphene film composite structure is scooped out with a clean cover glass and immersed in deionized water to remove residual etching solution;
[0076] The cleaned support layer-graphene film composite structure is picked up with the hydrophilic treated substrate, the graphene film is brought into contact with the substrate, and first dried to obtain the support layer-graphene film-substrate composite structure;
[0077] After removing the support layer from the support layer-graphene film-substrate composite structure, the composite structure is sequentially immersed in acetone, immersed in isopropyl alcohol, rinsed with anhydrous ethanol, and dried to obtain a substrate covered with a graphene film.
[0078] As an embodiment, the pretreatment is to place the copper foil in acetone, hydrochloric acid solution, deionized water and anhydrous ethanol in sequence for ultrasonic treatment, rinse with deionized water, and then dry it for the third time to obtain a clean copper foil; after polishing the clean copper foil, rinse it with deionized water and anhydrous ethanol in sequence, and then dry it for the fourth time. After annealing the polished copper foil in a reducing atmosphere, it is oxidized in air to obtain a pretreated copper foil; the mass concentration of the hydrochloric acid solution is 0.5-5%, and 1% in a specific embodiment; the power of each ultrasonic treatment is 40-90W, and 70W in a specific embodiment, and the time is 10-20 minutes, and 10 minutes in a specific embodiment; the rinsing time is 5-40 minutes, and 10 minutes in a specific embodiment; the third drying is blowing dry with nitrogen. Acetone solvent is used to remove oil, dust, and non-polar or weakly polar organic pollutants on the surface of copper foil. Hydrochloric acid solution can dissolve oxides and slight inorganic pollutants on the surface of copper foil. Deionized water can remove residual acid and water-soluble substances on the surface of copper foil. Anhydrous ethanol can further remove trace water-soluble and alcohol-soluble impurities on the surface of copper foil. Ultrasonic treatment helps various cleaning agents to better contact with the surface of copper foil for cleaning.
[0079] As an embodiment, the polishing process is as follows: placing the copper foil to be polished and another copper foil in a polishing liquid, connecting the copper foil to be polished to the anode of a DC power supply, and connecting the other copper foil to the cathode of the DC power supply, and performing electrochemical polishing using the voltage stabilization mode of the DC power supply. After the electrochemical polishing is completed, the copper foil to be polished is taken out and rinsed with deionized water and anhydrous ethanol in sequence; the polishing liquid includes phosphoric acid and polyethylene glycol 400; the volume ratio of the phosphoric acid to polyethylene glycol 400 is 2 to 4:1, and in a specific embodiment, it is 3:1; the preparation method of the polishing liquid is to add phosphoric acid and polyethylene glycol 400 to a beaker in sequence, and stir evenly until cooled to room temperature; the stirring is performed by stirring with a glass rod; the voltage of the DC power supply is 1.5 to 2.2 V, and in a specific embodiment, it is 1.8 V; the electrochemical polishing time is 0.5 to 4 hours, and in a specific embodiment, it is 2 hours; the deionized water rinse time is 5 to 40 minutes, and in a specific embodiment, it is 20 minutes; the anhydrous ethanol rinse time is 5 to 40 minutes, and in a specific embodiment, it is 15 minutes. The present invention electrochemically polishes the copper foil to smooth its surface and reduce surface roughness. A clean, smooth copper foil surface is essential for preparing large-area single-crystal graphene with low nucleation density. The present invention rinses the copper foil with deionized water and anhydrous ethanol to remove residual polishing liquid from the surface.
[0080] As an embodiment, the fourth drying is nitrogen drying. The present invention uses nitrogen drying to quickly dry the copper foil and avoid the formation of water stains on the surface of the copper foil.
[0081] As an embodiment, the reducing atmosphere includes a protective gas and a reducing gas; the protective gas is argon or nitrogen, specifically argon in a specific embodiment; the reducing gas is hydrogen; the annealing equipment is a tube furnace; the annealing temperature is 800-900°C, specifically 900°C in a specific embodiment, and the holding time is 30-120 minutes, specifically 60 minutes in a specific embodiment; the flow rate of the protective gas during the annealing process is 50-250 sccm, specifically 100 sccm in a specific embodiment, and the flow rate of the reducing gas is 20-100 sccm, specifically 20 sccm in a specific embodiment; the temperature of the oxidation treatment is 100-300°C, specifically 180°C in a specific embodiment, and the holding time is 20-60 minutes, specifically 30 minutes in a specific embodiment. The present invention further removes copper oxide and residual trace moisture on the surface of the copper foil by annealing in a high-temperature reducing atmosphere, and reduces the density of nucleation sites on the copper foil surface during graphene growth through oxidation treatment, which helps to obtain high-quality graphene films.
[0082] As an embodiment, the specific process of the chemical vapor deposition method is to heat the pretreated copper foil to 900-1100°C, and then perform a first heat preservation, a second heat preservation, a first cooling and a second cooling in sequence, which is 1040°C in a specific embodiment; the heating rate is 10-20°C / min, and 20°C / min in a specific embodiment; the atmosphere during the heating process is argon; the flow rate of the argon is 200-500sccm, and 250sccm in a specific embodiment; the atmosphere during the first heat preservation process is argon and hydrogen; the flow rate of the argon is 200-500sccm, and 250sccm in a specific embodiment; the flow rate of the hydrogen is 20-100sccm. cm, 20 sccm in a specific embodiment; the first insulation time is 60 to 150 min, 90 min in a specific embodiment; the atmosphere during the second insulation process is argon, hydrogen and carbon source gas; the carbon source gas is a hydrocarbon, methane, ethane or ethylene in a specific embodiment; the flow rate of the hydrocarbon is 1 to 10 sccm, 3 sccm in a specific embodiment; the second insulation time is 5 to 40 min, 20 min in a specific embodiment; the first cooling is to stop heating, and after cooling for 5 to 15 min, stop introducing the carbon source gas, 10 min in a specific embodiment; the second cooling is to cool to room temperature in an atmosphere of argon and hydrogen.
[0083] The high temperature environment of the chemical vapor deposition method in the present invention can provide energy for the decomposition of the carbon source gas on the surface of the copper foil and the diffusion and recombination of carbon atoms. The present invention adopts a chemical vapor deposition temperature within the above range, which can not only avoid the low graphene nucleation density and incomplete growth due to the slow reaction rate caused by too low temperature, but also avoid copper evaporation, substrate melting or excessive etching of graphene due to too high temperature. The chemical vapor deposition temperature within the above range adopted by the present invention is conducive to the surface diffusion of carbon atoms, so that single crystal nuclei have more opportunities to grow, thereby increasing the graphene grain size, reducing grain boundaries, and improving the quality of graphene films. In addition, the growth of graphene on copper foil follows a self-limiting growth mechanism (the first layer of coverage hinders the subsequent adsorption and decomposition of the carbon source). The chemical vapor deposition temperature within the above range adopted by the present invention is also the key to obtaining a single-layer graphene film.
[0084] The type and concentration of carbon source during chemical vapor deposition (CVD) have a significant impact on the growth rate, nucleation sites, and defect density of graphene. Different carbon sources have different decomposition temperatures, which will affect the growth kinetics and nucleation behavior of graphene. Excessively high carbon source concentrations will significantly increase the graphene nucleation density and growth rate, forming graphene with multiple grain boundaries and high defects, and may break through the self-limiting mechanism, causing a second layer or even multiple layers to nucleate and grow in the covered area (especially at grain boundaries, defects, or steps). During the graphene growth process, hydrogen has the functions of reducing copper foil (even at high temperatures, trace amounts of oxygen or water vapor may be present), etching weakly bound carbon atoms in graphene (such as defect sites, edges, and small grains) (the key to regulating grain size: an appropriate amount of hydrogen can inhibit the formation of small nuclei and stabilize the growth of large nuclei, thereby increasing the size of graphene grains; however, excessive hydrogen will cause excessive etching, resulting in slow growth or even failure to form a film.), regulating the decomposition rate of hydrocarbons on the copper surface, passivating graphene edges, and inhibiting multilayer formation. The present invention rationally controls the hydrogen-carbon ratio to achieve the preparation of low-defect, large-area single-layer graphene.
[0085] Parameters such as growth time, gas flow rate, and heating and cooling rates must be rationally controlled based on the carbon source type, temperature, atmosphere ratio, and reaction chamber geometry. Insufficient growth time prevents the graphene islands from completely covering the substrate, resulting in low coverage. When growth time is long enough, the graphene single crystals connect to form a continuous film. Excessive growth time under suboptimal conditions (such as high methane concentration and low temperature) may increase the likelihood of multilayer islands or lead to degradation of the already grown graphene (e.g., excessive hydrogen etching). The flow rate influences the flow field within the reaction chamber and the thickness of the gas boundary layer on the substrate surface. A higher flow rate can thin the boundary layer, promoting mass transfer of reactants to the substrate surface and byproducts away from the surface, helping to increase growth rate and film uniformity (especially for large-area growth). Sufficient gas flow facilitates rapid replacement of the gas within the reaction chamber, maintaining the stability of the set gas ratio. The heating rate influences the recrystallization process and final grain size / orientation of the copper grains, further impacting the catalytic activity of the copper surface. This is due to the different thermal expansion coefficients of graphene and copper. Rapid cooling generates significant thermal stress, causing graphene to wrinkle, crack, and even peel from the copper foil. During the cooling process, the atmosphere (especially H2) affects the final graphene doping level (hole doping), and excessively high hydrogen concentrations (low carbon source concentrations) at high temperatures can erode the graphene during cooling. Therefore, by precisely controlling the copper foil's pretreatment state and parameters such as temperature and atmosphere, the present invention can produce large-area, uniform, high-quality single-layer graphene, laying the foundation for the construction of high-performance palladium nanoparticle-graphene hydrogen sensors.
[0086] As an embodiment, the spin coating device is a spin coater; the transfer medium includes PMMA or PDMS, specifically PMMA; the spin coating speed is 2000-4000 rpm, specifically 3000 rpm, and the time is 0.5-3 min, specifically 1.5 min; the curing temperature is 50-80°C, specifically 70°C, and the time is 30-60 min, specifically 30 min; the etching solution is a ferric chloride solution; the concentration of the ferric chloride solution is 1-3 mol / L, specifically 2 mol / L; the etching time is 3-6 h, specifically 4 h. ; The immersion in deionized water is repeated 3 to 10 times, and 6 times in the specific embodiment; the specific process of the immersion in deionized water is as follows: after immersing in deionized water, the support layer-graphene film composite structure is picked up with a clean cover glass and immersed in new deionized water; the immersion time for each time is 5 to 30 minutes, and 20 minutes in the specific embodiment; the substrate is a silicon wafer, SiC wafer or aluminum oxide wafer with an oxide layer, and a silicon wafer with an oxide layer in the specific embodiment; the component of the oxide layer is SiO2, and the thickness is 200 to 500 nm, and 300 nm in the specific embodiment; the hydrophilic treatment is to place the substrate in a piranha solution and then rinse with deionized water to remove residual piranha The solution is then placed in acetone, isopropanol, anhydrous ethanol, deionized water and anhydrous ethanol for ultrasonic cleaning, and finally subjected to argon plasma treatment to obtain a hydrophilic substrate; the piranha solution includes a sulfuric acid solution and a hydrogen peroxide solution; the volume ratio of the sulfuric acid solution to the hydrogen peroxide solution is 7:3; the concentration of the sulfuric acid solution is 90-100%, and in a specific embodiment, it is analytically pure; the mass fraction of the hydrogen peroxide solution is 3-50%, and in a specific embodiment, it is 30%; the soaking time is 10-50 minutes, and in a specific embodiment, it is 30 minutes, and the temperature is 60-80°C, and in a specific embodiment, it is 80°C; the rinsing time is 5-20 minutes, and in a specific embodiment, it is The ultrasonic power of each ultrasonic cleaning is 40-90W, 70W in the specific embodiment, and the time is 10-20min, 10min in the specific embodiment; the flow rate of argon gas in the argon plasma treatment is 10-200sccm, 50sccm in the specific embodiment, the power is 30-70W, 60W in the specific embodiment, and the time is 5-10min, 10min in the specific embodiment; the first drying is drying after standing at room temperature; the standing time at room temperature is 6-24h, 12h in the specific embodiment; the drying temperature is 60-80℃, 70℃ in the specific embodiment, and the time is 0.5-1h, 0.5h; when the substrate is a silicon wafer with an oxide layer, the contact between the graphene film and the substrate is that the graphene film contacts the oxide layer of the silicon wafer with the oxide layer; the present invention does not specifically limit the method of removing the support layer, and methods well known in the art can be used. In a specific embodiment of the present invention, the method of removing the support layer is to soak in acetone for 6 to 24 hours, and in a specific embodiment, for 12 hours; soak in isopropyl alcohol for 10 to 30 minutes, and in a specific embodiment, for 10 minutes; rinse with anhydrous ethanol for 5 to 20 minutes, and in a specific embodiment, for 10 minutes; and the second drying is to blow dry with nitrogen.
[0087] As an embodiment, the thickness of the palladium nanofilm is 3 to 100 nm, and in a specific embodiment, it is 5 nm; the method of coating the palladium nanofilm is electron beam coating, thermal evaporation coating or magnetron sputtering coating, and in a specific embodiment, it is electron beam coating; the target material used for coating the palladium nanofilm is a palladium target; the purity of the palladium target is 99.9 to 99.999%, and in a specific embodiment, it is 99.99%; the vacuum degree of the electron beam coating is 2×10 -4 ~7×10 -4 Pa, in the specific embodiment, is 5×10 -4 Pa, the current is 80-120 mA, 90 mA in the specific embodiment, the voltage is 6-10 kV, 8.20 kV in the specific embodiment, and the evaporation rate is In a specific embodiment,
[0088] As an embodiment, the protective gas is argon; the flow rate of the argon is 50 to 200 sccm, and is 100 sccm in a specific embodiment; the temperature of the heat treatment is 400 to 650°C, and is 500°C in a specific embodiment; the holding time is 1 to 3 hours, and is 2 hours in a specific embodiment; the heating rate to the heat treatment temperature is 5 to 20°C / min, and is 15°C / min in a specific embodiment.
[0089] As an embodiment, the activation treatment is to carry out hydrogenation treatment in a reducing atmosphere and oxidation treatment in an oxygen-containing atmosphere in sequence; the reducing atmosphere includes hydrogen and argon; the flow rate of the hydrogen is 5 to 50 sccm, and is 20 sccm in a specific embodiment; the flow rate of the argon is 20 to 100 sccm, and is 80 sccm in a specific embodiment; the temperature of the hydrogenation treatment is 300 to 650°C, and is 500°C in a specific embodiment; the holding time is 10 to 60 minutes, and is 20 to 30 minutes in a specific embodiment; the oxygen-containing atmosphere includes oxygen and argon; the The oxygen content in the oxygen atmosphere is 1 to 100 ppm, and is 1 ppm in a specific embodiment; the flow rate of the oxygen-containing atmosphere is 10 to 200 sccm, and is 100 sccm in a specific embodiment; the temperature of the oxidation treatment is 300 to 650° C., and is 500° C. in a specific embodiment; the holding time is 5 to 60 minutes, and is 10 to 30 minutes in a specific embodiment; the activation treatment is repeated; the number of repetitions is 1 to 10 times, and is 1 time in a specific embodiment; after the activation treatment is completed, the activation treatment further includes: cooling the product after the activation treatment to room temperature in the oxygen-containing atmosphere with the furnace.
[0090] The present invention hydrogenates a graphene composite film bonded with palladium nanoparticles obtained by heat treatment in a reducing atmosphere. H enters the palladium lattice gap, causing the palladium nanoparticles to expand in volume, resulting in strong lattice distortion and stress concentration in the graphene carrier. Specifically, the C-C bonds within the palladium-graphene interface are elongated, the lattice around the interface is squeezed, and the C-C bonds are shortened. Subsequently, an oxidation treatment is performed in an oxygen-containing atmosphere. At this time, the hydrogen concentration decreases, hydrogen in the palladium is precipitated, the volume shrinks, and the graphene lattice recovers. This repeated expansion-contraction tensile / compressive strain destroys part of the graphene lattice, forming unstable carbon sites. The unstable carbon sites around the interface are exposed to the atmosphere and form oxygen-containing groups such as COC, C=O, and C-OH under the action of low-concentration oxygen. The hydrogen concentration, flow rate, hydrogenation temperature, and treatment time during the activation treatment determine the diffusion rate and depth of hydrogen atoms within the palladium particles, thereby affecting the volume expansion of the palladium after hydrogen absorption and the degree of graphene lattice distortion. High hydrogen concentrations, hydrogen flow rates, high temperatures, and long treatment times can accelerate the rate of hydrogen absorption by palladium, promoting the volume expansion of palladium particles. Combined with repeated hydrogenation-oxidation treatments, this facilitates the introduction of defects into graphene, providing abundant active sites for subsequent interface modification with oxygen groups. However, excessive hydrogen absorption will destroy the intrinsic structure of graphene, impair its electrical properties, and reduce carrier mobility, hindering the construction of highly sensitive hydrogen sensors. Excessively low hydrogenation levels, on the other hand, hinder the introduction of interfacial oxygen species, making it impossible to effectively improve the low sensitivity, slow recovery, and even incomplete recovery of existing palladium-graphene hydrogen sensors. Therefore, by varying the atmosphere during the activation treatment, the interfacial oxygen species content and the physicochemical properties of palladium and graphene can be controlled, thereby achieving regulation of hydrogen sensing performance.
[0091] The second method provided by the present invention comprises the following steps:
[0092] The suspension of polymer microspheres is self-assembled in water through the air-liquid interface to form a polymer microsphere array;
[0093] The polymer microsphere array is pulled out using a substrate covered with a graphene film, so that the polymer microsphere array and the graphene film overlap, and dried to obtain a polymer microsphere-graphene composite film;
[0094] After plating a palladium nanofilm on the polymer microsphere array of the polymer microsphere-graphene composite film, heat treatment is performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure.
[0095] As an embodiment, the polymer microspheres are polyethylene (PS) microspheres; the particle size of the polymer microspheres is 20 nm to 5 μm, and in specific embodiments, it is 100 nm, 500 nm or 1 μm; the suspension of the polymer microspheres includes a commercial solution of the polymer microspheres and a surfactant; the concentration of the polymer microspheres in the commercial solution of the polymer microspheres is 0.5 to 2.5 wt%, and in specific embodiments, it is 2.5 wt%; the surfactant is anhydrous ethanol; the volume ratio of the commercial solution of the polymer microspheres to the surfactant is 0.2 to 1.5:1, and in specific embodiments, it is 0.5:1, 0.6:1 or 1:1; the preparation method of the suspension of the polymer microspheres is to mix the commercial solution of the polymer microspheres and the surfactant and perform ultrasonic dispersion; the power of the ultrasonic dispersion is 40 to 90 W, and in specific embodiments, it is 70 W, and the time is 10 to 30 min, and in specific embodiments, it is 30 min.
[0096] As an embodiment, the water is deionized water; the polymer microspheres in the polymer microsphere array are hexagonally close-packed; the process of self-assembly at the air-liquid interface is: the hydrophilic treated coverslip is tilted and placed in a culture dish, water is poured in, and a portion of the hydrophilic treated coverslip is exposed to the air; the suspension of polymer microspheres is dropped on the coverslip exposed to the air, the suspension of polymer microspheres first diffuses on the coverslip, and slowly diffuses to the interface of water-air-coverslip under the action of gravity, and then gradually self-assembles in the water to form a polymer microsphere array; the equipment used for the dropwise addition is a micropipette; the dropwise addition amount of the polymer microsphere suspension is 10 to 100 μL, and 20 μL in a specific embodiment; the size of the coverslip is 2.5×2.5 cm 2 ; The hydrophilic treatment is to subject the cleaned coverslip to argon plasma treatment; the flow rate of argon gas in the argon plasma treatment is 10 to 200 sccm, and 10 sccm in a specific embodiment; the power of the argon plasma treatment is 30 to 70 W, and 50 W in a specific embodiment, and the time is 5 to 10 minutes, and 6 minutes in a specific embodiment; before the hydrophilic treated coverslip is tilted and placed in a culture dish, it also includes: pre-treating the culture dish; the pre-treatment is to dry it after cleaning; the drying temperature is 40 to 100°C, and 70°C in a specific embodiment, and the time is 30 to 60 minutes, and 30 minutes in a specific embodiment.
[0097] As an embodiment, the pulling process is: slowly inserting the substrate covered with the graphene film into water, pulling out the polymer microsphere array on the surface of the liquid, and making the polymer microsphere array and the graphene film overlap; the drying is drying after standing; the standing temperature is room temperature, the time is 0.5 to 12 hours, and the specific embodiment is 4 to 12 hours; the drying temperature is 40 to 80°C, and the specific embodiment is 60 to 70°C, and the time is 10 to 60 minutes, and the specific embodiment is 30 minutes. The present invention removes residual moisture by standing and then drying after the water evaporates. The present invention transfers the grown graphene film to the substrate intact and without damage to facilitate the construction of subsequent devices.
[0098] In the present invention, the preparation method of the substrate covered with graphene film, the method of plating the palladium nanofilm, and the heat treatment process in the second method are the same as those in the first method and will not be repeated here.
[0099] In method 2, the thickness of the palladium nanofilm refers to the thickness of the palladium nanofilm at the plane. Due to the concave and convex morphology caused by the polymer microsphere array, the thickness of the palladium nanofilm on the surface of the microsphere is uneven, with the top center of the sphere being thicker and the edges being thinner. Due to the obstruction of the microspheres, the thickness of the palladium nanofilm at the gap between the microspheres is lower than the thickness of the palladium nanofilm at the position without microspheres, which provides conditions for subsequent heat treatment to obtain a highly dispersed palladium nanoparticle array.
[0100] In the second method of the present invention, heat treatment is used to remove the polymer microspheres and obtain regularly arranged, small-sized, highly dispersed palladium nanoparticles. During the heating process, the polymer microspheres gradually decompose. A relatively low heating rate helps reduce carbon residue, avoiding structural collapse caused by the rapid decomposition of the polymer microspheres, the generation of carbon black residue, which impairs device performance and hinders the production of a uniform, highly dispersed palladium nanoparticle array. A sufficiently high heat treatment temperature and a sufficiently long holding time facilitate the complete decomposition of the polymer microspheres and the sufficient removal of surface carbon residues.
[0101] In addition, the present invention can regulate the coverage of graphene surface palladium nanoparticles by changing parameters such as palladium nanofilm thickness, polymer microsphere particle size, and heat treatment temperature, thereby further realizing the regulation of hydrogen sensor performance. Specifically, high temperature promotes the agglomeration of palladium atoms, so that the palladium nanofilm forms separated palladium particles, and lower heat treatment temperature is conducive to obtaining palladium nanoparticles with smaller size. When using polymer microsphere templates, due to the influence of palladium nanofilm thickness, the distribution of palladium nanoparticles obtained after heat treatment inherits the polymer microsphere array arrangement rule, i.e., larger palladium nanoparticles are formed at the center position of the polymer microsphere (palladium nanofilm is thicker), and small-sized palladium nanoparticles are formed all around, so that a palladium nanoparticle array with regular arrangement, high dispersibility, and high coverage can be obtained, and the regulation of the distribution state of palladium nanoparticles can be realized by changing the polymer microsphere size. When the thickness of the palladium nanofilm is low, the size of the palladium particles after heat treatment is small, but the palladium loading is low and the palladium coverage is low, which is not conducive to improving the sensitivity of the hydrogen sensor; when the palladium nanofilm is thicker, the palladium loading is high, and the palladium nanoparticle-graphene composite structure has a higher active site density, which promotes the response of the hydrogen sensor to hydrogen; when the palladium nanofilm is too thick, it will completely cover the surface of the polymer microspheres and form an uneven palladium shell, and the graphene-loaded palladium nanoparticle structure cannot be obtained. The thickness of the palladium nanofilm forming the palladium shell is related to the particle size of the polymer microspheres and the heat treatment temperature, and the process parameters need to be reasonably selected.
[0102] The third method provided by the present invention comprises the following steps:
[0103] The product after heat treatment in the second method is repeatedly activated to obtain a palladium nanoparticle-graphene composite structure.
[0104] In the present invention, the activation treatment process in the third method is consistent with the activation treatment process in the first method, and will not be repeated here.
[0105] In method three, the present invention proposes a method combining a polymer microsphere array template method with high-temperature treatment to obtain highly dispersed palladium nanoparticles. Specifically, an ordered microsphere template is constructed on the graphene surface through a gas-liquid interface self-assembly process, and then combined with coating and annealing technology to achieve the regulation of the size distribution of palladium nanoparticles. This method breaks through the limitations of random nucleation of metal particles in traditional loading processes, solves the technical problems of low coverage and easy agglomeration of palladium nanoparticles on the surface of graphene carriers, significantly improves the contact area and active site density of palladium nanoparticles-graphene interface, and is beneficial to the electron transfer between palladium-hydrogen-graphene during the hydrogen response process. Furthermore, to address the slow recovery rate caused by the strong Pd-H bond during hydrogen sensing, the present invention uses a hydrogenation-oxidation strategy, utilizing the dynamic, reversible process of palladium volume expansion upon hydrogen absorption and contraction upon dehydrogenation to induce graphene lattice distortion. Combined with the effect of low-concentration oxygen, this creates localized oxygen species modification sites on the graphene at the interface, significantly reducing the hydrogen overflow barrier and promoting the migration of hydrogen atoms from the palladium surface to the graphene carrier. This effectively inhibits the deep diffusion of hydrogen into the palladium bulk, significantly improving the sensitivity and recovery rate of the hydrogen sensor. The present invention can effectively regulate the palladium nanoparticle-graphene interface structure without affecting the graphene away from the interface, thereby maximizing the advantages of graphene's excellent electrical properties, such as high carrier mobility. Under the dual mechanisms of optimizing hydrogen diffusion paths by interfacial oxygen-containing groups and improving hydrogen diffusion efficiency by high-density active sites, the hydrogen sensor using the palladium nanoparticle-graphene composite structure prepared by the present invention as a hydrogen-sensitive material has broken through the performance limit of a single modification strategy and achieved a synergistic gain in sensing performance, enabling it to simultaneously possess the excellent performance of ultra-high sensitivity and rapid and complete recovery at room temperature, realizing the detection of low-concentration hydrogen at room temperature with high accuracy and good safety, and having good commercial prospects.
[0106] The present invention also provides a palladium nanoparticle-graphene composite structure prepared by the preparation method described in the above technical solution, comprising a graphene film, palladium nanoparticles bonded to the surface of the graphene film through Pd-C bonds, and oxygen-containing groups modified on the surface of the graphene film;
[0107] When the preparation method is method 1, the average particle size of the palladium nanoparticles is 40 to 80 nm, and in a specific embodiment, it is 61 nm; the coverage is 15 to 30%, and in a specific embodiment, it is 24%; the atomic proportion of the oxygen-containing groups in the graphene film is 15 to 50%, and in a specific embodiment, it is 25%;
[0108] When the preparation method is method 2, the palladium nanoparticles include large-size palladium nanoparticles arranged in a hexagonal pattern and small-size palladium nanoparticles dispersed between the large-size palladium nanoparticles; the particle size difference between the large-size palladium nanoparticles and the small-size palladium nanoparticles is 5 to 400 nm, and in a specific embodiment, it is 20 to 100 nm; the coverage of the palladium nanoparticles is 20 to 80%, and in a specific embodiment, it is 36%; the atomic proportion of the oxygen-containing groups in the graphene film is 1 to 15%, and in a specific embodiment, it is 13%;
[0109] When the preparation method is method three, the palladium nanoparticles include large-size palladium nanoparticles arranged in a hexagonal pattern and small-size palladium nanoparticles dispersed between the large-size palladium nanoparticles; the particle size difference between the large-size palladium nanoparticles and the small-size palladium nanoparticles is 5 to 400 nm, and in a specific embodiment, it is 20 to 100 nm; the oxygen-containing groups are distributed around the contact interface between the graphene film and the palladium nanoparticles; the coverage rate of the palladium nanoparticles is 20 to 80%, and in a specific embodiment, it is 36%; the atomic proportion of the oxygen-containing groups in the graphene film is 15 to 50%, and in a specific embodiment, it is 27%.
[0110] As an embodiment, the particle size of the large-size palladium nanoparticles is 20 to 500 nm, and in a specific embodiment, it is 50 nm; the particle size of the small-size palladium nanoparticles is 1 to 100 nm, and in a specific embodiment, it is 10 nm.
[0111] As an embodiment, the oxygen-containing group includes one or more of C-OH, COC, C=O and O=C-OH.
[0112] The present invention also provides an application of the palladium nanoparticle-graphene composite structure described in the above technical solution in a hydrogen sensor.
[0113] The present invention also provides a hydrogen sensor, comprising a palladium nanoparticle-graphene composite structure and electrodes deposited at both ends of the surface of the palladium nanoparticle-graphene composite structure; the palladium nanoparticle-graphene composite structure is the palladium nanoparticle-graphene composite structure described in the above technical solution.
[0114] As an embodiment, the electrode is a Cr-Au composite film; the Cr-Au composite film includes a Cr film and an Au film supported on the surface of the Cr film; the thickness of the Cr film is 5 to 20 nm, and in a specific embodiment, it is 20 nm; the thickness of the Au film is 20 to 50 nm, and in a specific embodiment, it is 50 nm; the preparation method of the Cr film and the Au film is coating; the coating includes thermal evaporation coating, electron beam coating or magnetron sputtering coating, and in a specific embodiment, it is thermal evaporation coating; the target material used for the thermal evaporation coating is an Au target and a chromium target, and the vacuum degree is 2×10 -4~7×10 -4 Pa, in the specific embodiment, is 5×10 -4 Pa, current 80-170 mA, in the specific embodiment, the current for Au film plating is 130 mA, the current for Cr film plating is 170 mA, the voltage is 6-10 kV, in the specific embodiment it is 2.1 kV, the evaporation rate is In a specific embodiment,
[0115] As an embodiment, the hydrogen sensor is a resistive device.
[0116] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention, but they should not be understood as limiting the scope of protection of the present invention.
[0117] Example 1
[0118] (1) Preparation of high-quality graphene films
[0119] First, the copper foil was placed in acetone, 1wt% hydrochloric acid solution, deionized water, and anhydrous ethanol in sequence and ultrasonically treated at 70W power for 10 minutes each. The residual solvent on the surface was then rinsed with deionized water for 10 minutes, and finally dried with nitrogen to obtain a clean copper foil. Subsequently, the clean copper foil was electrochemically polished: ① Prepare the polishing solution, add phosphoric acid and polyethylene glycol 400 in a volume ratio of 3:1 into a beaker, stir evenly with a glass rod until cooled to room temperature; ② Place the copper foil to be polished and another copper foil in the polishing solution, connect the copper foil to the anode of the DC power supply, and the other copper foil to the polishing solution. A copper foil was connected to the cathode and electrochemically polished for 2 hours using a DC power supply in voltage regulation mode at 1.8V. ③ After electrochemical polishing, the copper foil was removed and rinsed with deionized water for 20 minutes to remove the polishing liquid on the surface of the copper foil. It was then rinsed with anhydrous ethanol for 15 minutes and then dried with nitrogen. The polished copper foil was placed in a tube furnace and annealed at 900°C for 60 minutes in an atmosphere of 100 sccm argon and 20 sccm hydrogen. The annealed copper foil was then oxidized in air at 180°C for 30 minutes to obtain the pretreated copper foil.
[0120] A graphene film was grown on the surface of the pretreated copper foil by chemical vapor deposition, with the following specific parameters: ① placing the pretreated copper foil in a tube furnace and heating it to 1040° C. at a heating rate of 20° C. / min in an atmosphere of 250 sccm argon; ② keeping it at the aforementioned temperature for 90 minutes in an atmosphere of 250 sccm argon and 20 sccm hydrogen; ③ introducing 3 sccm methane as a carbon source gas, keeping it at this temperature for 20 minutes, then stopping the heating, turning off the carbon source gas after 10 minutes, and cooling it to room temperature in a protective atmosphere of 250 sccm argon and 20 sccm hydrogen, and then removing the copper foil covered with the graphene film;
[0121] (2) Transfer of graphene film
[0122] First, a layer of PMMA was spin-coated on the surface of the graphene-coated copper foil as a support layer using a spin coater. 50 μL PMMA was dripped onto the copper foil surface using a pipette gun. After ensuring that it covered the copper foil surface and no bubbles were generated, the spin coater was started at 3000 rpm for 1.5 min. The spin-coated sample was dried at 70 ° C for 30 min to solidify the PMMA to form a support layer. The sample was placed in a 2 mol / L ferric chloride solution and etched for 4 h to remove the copper foil. The remaining support layer-graphene composite structure floated on the liquid surface. A clean cover glass was used to pick up the floating support layer-graphene composite structure and soaked in deionized water for 20 min. It was then picked up and placed in new deionized water. The operation was repeated 6 times. A silicon wafer with a 300 nm oxide layer (SiO2) was selected as the substrate. The substrate was placed in a piranha solution (volume ratio of 7 : 3% concentrated sulfuric acid (analytical grade) and 30% hydrogen peroxide solution) was immersed in 80 ° C for 30 min, and then rinsed with deionized water for 20 min; then placed in acetone, isopropanol, anhydrous ethanol, deionized water, and anhydrous ethanol in sequence, and ultrasonically cleaned for 10 min each at 70 W power, and then subjected to argon plasma treatment for 10 min, with an argon flow rate of 50 sccm and a power of 60 W. The cleaned support layer-graphene composite structure was fished out with the treated silicon wafer to make the SiO2 layer and the graphene film closely fit. After directly peeling off the support layer, it was placed at room temperature for 12 h, then placed in an oven and dried at 70 ° C for 0.5 h; finally, the sample was immersed in acetone for 12 h and in isopropanol for 10 min; rinsed with anhydrous ethanol for 10 min, and then dried with nitrogen to obtain a substrate covered with a graphene film.
[0123] Figure 1 This is an optical micrograph of the graphene film transferred onto the Si / SiO2 substrate in Example 1. Figure 1 No wrinkles or damage were observed in the graphene film.
[0124] Figure 2 is the Raman graph of the graphene film after transfer in Example 1. Figure 2 It can be obtained that the graphene obtained in Example 1 is D / I G ≈0.27, and the defect density is low, that is, a clean, flat, and high-quality graphene film transferred to the Si / SiO2 substrate is obtained by the above method.
[0125] Example 2
[0126] The graphene film transfer steps are the same as those in Example 1, except that Figure 3As shown, ① a 2.5wt% solution of PS microspheres with a particle size of 1μm monodispersed in H2O was mixed with anhydrous ethanol at a volume ratio of 0.5:1, and ultrasonically dispersed at 70W power for 30min to obtain a suspension of PS microspheres; ② a culture dish with a size of 2.5×2.5cm was placed 2 After the coverslip is cleaned, it is treated with argon plasma (argon flow rate 10 sccm, power 50 W) for 6 min; the hydrophilic coverslip is tilted and placed in a culture dish that has been dried at 70°C for 30 min, and deionized water is poured into it; ③ 20 μL of the PS microsphere suspension is slowly added dropwise to the coverslip exposed to the air using a micropipette, and the PS microsphere suspension first diffuses on the coverslip and then slowly diffuses to the water / air / coverslip trilayer under the action of gravity. ④ A silicon wafer covered with graphene film was slowly inserted into the deionized water to pull out the single-layer PS microsphere array on the water surface, so that the single-layer PS microsphere array overlapped with the graphene film area; ⑤ The sample was left to stand at room temperature for 12 hours, and after the water evaporated, it was dried at 60℃ for 30 minutes to remove the residual water, thus obtaining a PS microsphere array-graphene film-silicon wafer composite structure.
[0127] Figure 4 This is a SEM image of the array of PS microspheres (1 μm in diameter) on the surface of the graphene film in Example 2. Figure 4 It can be seen that the method of the present invention can obtain a PS microsphere array-graphene film composite structure with a diameter of 1 μm.
[0128] Example 3
[0129] The difference from Example 2 is that a 2.5 wt% solution of PS microspheres with a particle size of 500 nm monodispersed in H2O is mixed with anhydrous ethanol at a volume ratio of 0.6:1 and ultrasonically dispersed for 30 minutes. The rest of the process is the same as Example 2.
[0130] Figure 5 This is a SEM image of the PS microsphere (diameter 500nm) array on the graphene film surface in Example 3. Figure 5 It can be seen that the method of the present invention can obtain a PS microsphere array-graphene film composite structure with a diameter of 500 nm.
[0131] Example 4
[0132] The difference from Example 2 is that a 2.5 wt% solution of PS microspheres with a particle size of 100 nm monodispersed in H2O is mixed with anhydrous ethanol at a volume ratio of 1:1 and ultrasonically dispersed for 30 minutes. The rest of the process is the same as Example 2.
[0133] Figure 6This is a SEM image of the PS microsphere (diameter of 100 nm) array on the graphene film surface in Example 4. Figure 6 It can be seen that the method of the present invention can obtain a PS microsphere array-graphene film composite structure with a diameter of 100 nm.
[0134] Example 5
[0135] The substrate covered with graphene film prepared in Example 1 was deposited with a uniform palladium nanofilm with a thickness of 5 nm on the graphene surface by electron beam coating equipment. The target material was 99.99% palladium particles, and the vacuum degree was 5×10 -4 Pa, current 90mA, voltage 8.20kV, evaporation rate is The sample was then placed in a tube furnace, heated to 500°C at a heating rate of 15°C / min in an argon atmosphere of 100 sccm, and heat treated for 2 hours to obtain a palladium nanoparticle-graphene composite film (Pd-Gr).
[0136] The morphology of the palladium nanoparticles in the palladium nanoparticle-graphene composite film prepared in Example 5 is as follows: Figure 7 As shown, statistics show that the average particle size of palladium nanoparticles is about 66 nm and the coverage is about 23%.
[0137] Example 6
[0138] The single-layer PS microsphere array-graphene film-silicon wafer composite structure prepared in Example 4 was subjected to an electron beam coating device to deposit a uniform palladium nanofilm with a thickness of 5 nm on the surface of the PS microspheres. Other parameters were the same as those in Example 5 to obtain palladium nanoparticles with regular arrangement, small size, and high dispersion. The palladium nanoparticle-graphene composite structure (Pd PS -Gr).
[0139] The morphology of the palladium nanoparticles in the palladium nanoparticle-graphene composite structure prepared in Example 6 is as follows: Figure 8 As shown, the statistics can be obtained (such as Figure 9 As shown), the average particle size of the palladium nanoparticles is about 12 nm, and the coverage is about 36%. Compared with the case where no PS microsphere array template is used (Example 5), the particle size of the palladium nanoparticles is significantly reduced and the coverage is improved.
[0140] Figure 10 Figure 2 shows the average size and coverage of palladium nanoparticles prepared using PS microspheres of varying diameters as templates. The figure shows that the palladium nanoparticles obtained using PS microsphere arrays as templates have smaller average particle sizes and higher coverage. Furthermore, as the PS microsphere diameter decreases, the coverage of the palladium nanoparticles on the graphene surface increases. This facilitates electron transfer between palladium and graphene during the hydrogen response, improving sensor sensitivity.
[0141] Example 7
[0142] With the help of a mask, a 20 nm Cr film and a 50 nm Au film were deposited on both ends of the surface of the palladium nanoparticle-graphene composite film (Pd-Gr) prepared in Example 5 by thermal evaporation equipment to form electrodes. The target materials used were 99.99% Au sheet and chromium powder, and the vacuum degree was 5×10 -4 Pa, voltage 2.1kV, evaporation current 130mA (Au film), 170mA (Cr film), evaporation rate Get the hydrogen sensor.
[0143] Example 8
[0144] With the help of a mask plate, the palladium nanoparticle-graphene composite structure (Pd PS -Gr) surface were respectively deposited with 20nm Cr film and 50nm Au film to form electrodes, and the electrode preparation method was the same as that in Example 7.
[0145] Figure 11 The response behavior of the hydrogen sensor in Example 7 and Example 8 to 2 vol% H2 at room temperature is: sensitivity Response = (R-R0) / R0×100%, where R0 is the initial resistance of the hydrogen sensor and R is the resistance after responding to the target gas. Figure 11 It can be seen that compared with Example 7, the sensitivity of the hydrogen sensor constructed with highly dispersed palladium nanoparticles obtained by the PS microsphere template method of the present invention (Example 8) is significantly improved.
[0146] Example 9
[0147] The substrate covered with graphene film prepared in Example 1 was deposited with a uniform palladium nanofilm with a thickness of 5 nm on the graphene surface by electron beam coating equipment. The target material was 99.99% palladium particles, and the vacuum degree was 5×10 -4 Pa, current 90mA, voltage 8.20kV, evaporation rate is The sample was then placed in a tube furnace and treated at 500°C for 2 h in a 100 sccm argon atmosphere with a heating rate of 15°C / min. The atmosphere was then switched to 20 sccm hydrogen and 80 sccm argon and maintained at 500°C for 30 min. The atmosphere was adjusted to 100 sccm O2 (argon diluted) with a concentration of 1 ppm. After 5 min, the sample was allowed to cool to room temperature in the furnace to obtain a palladium nanoparticle-graphene composite structure (Pd-Gr-O H20% ), the average particle size of the obtained palladium nanoparticles was 61 nm and the coverage was 24%;
[0148] Figure 12The palladium nanoparticle-graphene composite film (Pd-Gr) prepared in Example 5 and the palladium nanoparticle-graphene composite structure (Pd-Gr-O H20% ) XPS C 1s spectrum and peak separation results. Figure 12 It can be seen that after activation treatment, the atomic proportion of oxygen-containing groups (including C-OH, COC, C=O, O=C-OH) is 25% (in unactivated Pd-Gr, the atomic proportion of oxygen-containing groups is only 11%).
[0149] With the help of a mask, a 20nm Cr film and a 50nm Au film were deposited on both ends of the surface of the palladium nanoparticle-graphene composite structure by thermal evaporation equipment to form electrodes. The target materials used were 99.99% Au target and chromium target, and the vacuum degree was 5×10 -4 Pa, voltage 8kV, evaporation current 130mA (Au film), 170mA (Cr film), evaporation rate Get the hydrogen sensor.
[0150] Figure 13 Shown are the actual picture and schematic diagram of the hydrogen sensor.
[0151] Figure 14 The response and recovery behavior diagram of the hydrogen sensor prepared in Example 9 to 2% H2 at room temperature. It can be seen from the figure that the recovery time is more than 5 minutes when not activated ( Figure 11 ) is shortened to less than 1 minute.
[0152] Example 10
[0153] The PS microsphere array-graphene film composite structure prepared in Example 4 was subjected to an electron beam coating device to deposit a uniform palladium nanofilm with a thickness of 5 nm on its surface. The coating, heat treatment and activation treatment methods were the same as those in Example 9 to obtain a palladium nanoparticle-graphene composite structure (Pd PS -Gr-O H20% ); The electrode preparation method is the same as that in Example 9 to obtain a hydrogen sensor.
[0154] Figure 15 The palladium nanoparticle-graphene composite structure (Pd PS -Gr) and the palladium nanoparticle-graphene composite structure prepared in Example 10 (Pd PS -Gr-O H20% ) XPS C 1s spectrum and peak separation results. Figure 15 It can be seen that after the interface is modified with oxygen species, the atomic proportion of oxygen-containing groups (including C-OH, COC, C=O, O=C-OH) is 27% (when the oxygen species are not modified, the atomic proportion of oxygen-containing groups is only 13%).
[0155] Figure 16 This is the response and recovery behavior diagram of the hydrogen sensor prepared in Example 10 to 10ppb-2% H2 at room temperature. Figure 17 This is a test chart of the repeatability response of the hydrogen sensor prepared in Example 10 to 100 ppm H2 at room temperature. Figure 18 This is a selectivity test chart of the hydrogen sensor prepared in Example 10 to 100 ppm H2, NH3, CO, SO2, and CH4 at room temperature.
[0156] from Figures 16-18 It can be seen that the hydrogen sensor has a response of more than 400% to 2% H2, a recovery time of 0.5 min, and a detection limit as low as 10 ppb, with good selectivity and repeatability.
[0157] Example 11
[0158] The hydrogenation treatment atmosphere is 50 sccm hydrogen and 50 sccm argon; the other parameters are the same as those in Example 10.
[0159] Figure 19 This is the response and recovery behavior diagram of the hydrogen sensor prepared in Example 11 to 1ppb-2% H2 at room temperature. Figure 19 It can be seen that the hydrogen sensor prepared in Example 11 has a response of more than 140% to 2% H2 at room temperature, a recovery time of 0.8 min, and a detection limit as low as 1 ppb.
[0160] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a palladium nanoparticle-graphene composite structure, characterized in that: Including method 1, method 2 or method 3; The method 1 comprises the following steps: After plating a palladium nanofilm on a substrate covered with a graphene film, heat treatment and repeated activation treatment are performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure; The activation treatment is carried out by hydrogenation treatment in a reducing atmosphere and oxidation treatment in an oxygen-containing atmosphere in sequence; The second method comprises the following steps: The suspension of polymer microspheres is self-assembled in water through the air-liquid interface to form a polymer microsphere array; The polymer microsphere array is pulled out using a substrate covered with a graphene film, so that the polymer microsphere array and the graphene film overlap, and dried to obtain a polymer microsphere-graphene composite film; After plating a palladium nanofilm on the polymer microsphere array of the polymer microsphere-graphene composite film, heat treatment is performed in a protective gas to obtain a palladium nanoparticle-graphene composite structure; The method three comprises the following steps: The product after heat treatment in the second method is repeatedly activated to obtain a palladium nanoparticle-graphene composite structure.
2. The preparation method according to claim 1, characterized in that The polymer microspheres are polyethylene microspheres; the particle size of the polymer microspheres is 20 nm to 5 μm.
3. The preparation method according to claim 1, characterized in that The thickness of the palladium nanofilm is 3-100 nm.
4. The preparation method according to claim 1, characterized in that The reducing atmosphere includes hydrogen and argon; the flow rate of the hydrogen is 5 to 50 sccm; the flow rate of the argon is 20 to 100 sccm; the temperature of the hydrogenation treatment is 300 to 650° C., and the holding time is 10 to 60 minutes.
5. The preparation method according to claim 1, characterized in that The oxygen-containing atmosphere includes oxygen and argon; the oxygen content in the oxygen-containing atmosphere is 1 to 100 ppm; the flow rate of the oxygen-containing atmosphere is 10 to 200 sccm; the temperature of the oxidation treatment is 300 to 650° C., and the holding time is 5 to 60 minutes.
6. The preparation method according to claim 1, characterized in that The heat treatment temperature is 400-650° C., and the holding time is 1-3 hours; the heating rate to the heat treatment temperature is 5-20° C. / min.
7. The preparation method according to claim 1, characterized in that The palladium nanofilm is plated by electron beam coating, thermal evaporation coating or magnetron sputtering coating.
8. The palladium nanoparticle-graphene composite structure prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The method comprises a graphene film, palladium nanoparticles bonded to the surface of the graphene film via Pd-C bonds, and oxygen-containing groups modified on the surface of the graphene film; When the preparation method is method 1, the average particle size of the palladium nanoparticles is 40 to 80 nm, and the coverage is 15 to 30%; the atomic proportion of the oxygen-containing groups in the graphene film is 15 to 50%; When the preparation method is method 2, the palladium nanoparticles include large-diameter palladium nanoparticles arranged in a hexagonal pattern and small-diameter palladium nanoparticles dispersed between the large-diameter palladium nanoparticles; the difference in particle size between the large-diameter palladium nanoparticles and the small-diameter palladium nanoparticles is 5 to 400 nm; the coverage of the palladium nanoparticles is 20 to 80%; and the atomic proportion of the oxygen-containing groups in the graphene film is 1 to 15%. When the preparation method is method three, the palladium nanoparticles include large-size palladium nanoparticles arranged in a hexagonal pattern and small-size palladium nanoparticles dispersed between the large-size palladium nanoparticles; the particle size difference between the large-size palladium nanoparticles and the small-size palladium nanoparticles is 5 to 400 nm; the oxygen-containing groups are distributed around the contact interface between the graphene film and the palladium nanoparticles; the coverage rate of the palladium nanoparticles is 20 to 80%; and the atomic proportion of the oxygen-containing groups in the graphene film is 15 to 50%.
9. Use of the palladium nanoparticle-graphene composite structure according to claim 8 in a hydrogen sensor.
10. A hydrogen sensor, characterized in that: It comprises a palladium nanoparticle-graphene composite structure and electrodes deposited on both ends of the surface of the palladium nanoparticle-graphene composite structure; the palladium nanoparticle-graphene composite structure is the palladium nanoparticle-graphene composite structure according to claim 8.
